Determination of Antioxidant Activities in Four Dominant Species of Trentepohlia (Trentepohliales, Chlorophyta) from East Khasi Hills, Meghalaya, India - Kharkongor, Diana; Ramanujam, Papiya (Current Aspects in Pharmaceutical Research and Development Vol. 8, 2022)
The present study examine the antioxidant activity of the four dominant species and study the participation of other antioxidant compounds such as phenolics besides the well known Carotenoids. The antioxidant properties of four Trentepohlia species (T. abietina, T. arborum, T. diffracta, and T. umbrina) were evaluated in vitro, and all four species were shown to be rich in phenolic compounds, a surprising finding. T. abietina extract, on the other hand, had the highest total phenolic component and flavonoid content, as well as the strongest scavenging action and the lowest IC50. The scavenging activity of the four Trentepohlia species extracts was observed to decrease in the following order T. abietina >T. arborum>T. diffracta>T. umbrina. Moreover, both DPPH radical scavenging activity and superoxide anion radical scavenging activity varied significantly between the four species. In case of reducing power, extracts of all four species were concentration dependent where high reducing power was observed at higher concentration and gradually decreased with decrease in concentration of the extracts. Comparing amongst the species, T. abietina again showed highest reducing power at all the concentrations. The result of correlation showed a positive increase in scavenging activities with increase in flavonoids content. This present scenario the scavenging effect exhibited by the extract of four species of Trentepohlia mainly the DPPH scavenging activity could be attributed to the presence of mainly flavonoids constituent. This clearly indicated that in this case, the scavenging effect exhibited by the extract of all four species of Trentepohlia mainly the DPPH scavenging activity could be attributed to the presence of mainly flavonoids constituent.